Zinc Industry - Hewitt, Ken (Woodhead Pub., 2000)
This looseleaf industry handbook provides a comprehensive and practical guide to the workings of the international zinc industry. Concise and lucid, it considers trading techniques and strategies for different market users and includes useful appendices on zinc specifications and the world's major zinc and lead mines. It is essential for all those involved in the industry. A comprehensive guide to the workings of the international zinc industryWritten by well known industry insidersExamines future trends in demand, trade and pricing.